The influence of yarn fineness and number of yarn layers on in-plane shear properties of 3-D woven fabric. (7th January 2020) - Guan, Liuxiang; Li, Jialu; Jiao, Ya'nan
The 3-D layer-to-layer angle-interlock woven fabric (LLAIWF) has good deformability on a complicated contour, which offers them a large application potential in the field of aerospace. This article mainly focuses on the influence of yarn fineness and number of yarn layers on in-plane shear properties of 3-D LLAIWF during bias extension. Two methods of varying the thickness of 3-D LLAIWF were designed: changing yarn fineness and changing the number of yarn layers. The deformation mechanism of LLAIWF in bias-extension test was analyzed. The effects of two methods on in-plane shear deformation were compared and analyzed. In addition to the data processing on the experimental curve, digital image correlation analysis was conducted on the test photographs, from which shear angles in different area shear angle were measured. The mesostructure of fabric during the bias-extension test was observed. The effect of decreasing yarn layers on the mesostructure of fabric was observed by cutting fabric. The results demonstrated that the yarn fineness and the number of yarn layers play a key role in the in-plane shear properties of 3-D LLAIWF. In addition, the changing of fabric thickness causes that the deformation is asymmetrical. The effect of warp yarn fineness is similar to that of weft yarn fineness during the bias-extension test. Reducing the internal yarns of the fabric created a gap, where the yarns were reduced. This gap will affect the deformability of the fabric.